2004
DOI: 10.1177/000348940411300610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glucocorticoids on Infiltrating Cells and Epithelial Cells of Nasal Polyps

Abstract: Glucocorticoids are known to be effective in the treatment of nasal polyps (NPs). To examine the mechanisms of their effect, we evaluated 1) the ability of glucocorticoids to induce the apoptosis of eosinophils and T lymphocytes in NPs, and 2) the ability of dexamethasone to down-regulate epithelial cell functions that relate to eosinophilic inflammation. In vitro and in vivo, glucocorticoids increased the apoptosis of both eosinophils and T lymphocytes in NPs. Dexamethasone inhibited the production of granulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 36 publications
0
26
0
1
Order By: Relevance
“…It has been reported that in lower airway diseases (e.g., asthma, bronchiolitis obliterans, chronic obstructive pulmonary disease, and cystic fibrosis), the pseudostratified airway surface epithelium is severely damaged and must regenerate to restore its defense functions [11]. The same results have also been found in the sinonasal epithelial cells from CRSwNP, such as up-regulation of MUC1, MUC4, and MUC8 [12,13]; down-regulation of MUC5AC [12,13] and TLR9 [14]; upexpression of VPF/VEGF [15,16] and LL-37 [17,18]; increased production of GM-CFS [19]; and staph invasion of sinonasal epithelial cells [20]. It is interesting that during the recovery or resolution phase of viral infections in the lower airways, the immune system must help to orchestrate tissue repair to restore normal lung architecture and function and prevent permanent defects in respiratory function [4••].…”
Section: Role Of Nasal Epithelium In Common Upper Airway Diseasesmentioning
confidence: 73%
“…It has been reported that in lower airway diseases (e.g., asthma, bronchiolitis obliterans, chronic obstructive pulmonary disease, and cystic fibrosis), the pseudostratified airway surface epithelium is severely damaged and must regenerate to restore its defense functions [11]. The same results have also been found in the sinonasal epithelial cells from CRSwNP, such as up-regulation of MUC1, MUC4, and MUC8 [12,13]; down-regulation of MUC5AC [12,13] and TLR9 [14]; upexpression of VPF/VEGF [15,16] and LL-37 [17,18]; increased production of GM-CFS [19]; and staph invasion of sinonasal epithelial cells [20]. It is interesting that during the recovery or resolution phase of viral infections in the lower airways, the immune system must help to orchestrate tissue repair to restore normal lung architecture and function and prevent permanent defects in respiratory function [4••].…”
Section: Role Of Nasal Epithelium In Common Upper Airway Diseasesmentioning
confidence: 73%
“…There are a few studies to determine the effect of glucocorticoids on apoptosis in nasal polyps [4,5,6]. However, these studies only identified the induction of apoptosis in the stromal cells, fibroblasts, eosinophils and T lymphocytes in nasal polyps by glucocorticoids in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids increased apoptosis in a variety of polymorphonuclear cells, such as eosinophils, T lymphocytes and fibroblasts in nasal polyps [5,6]. The mechanism of glucocorticoids-induced apoptosis performed in lymphoid cells, like thymocytes, has been identified through in vitro studies, however the exact signaling pathway for glucocorticoids induced apoptosis in nasal polyp remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Hamilos et al 15 noted a marked decrease in GM-CSF, but not in TNF-α, in an in vivo study of fluticasone use during one month. Watanabe et al 11 also found decreased GM-CSF levels in nasal polyp epithelial cells under GC therapy, which would explain reduced eosinophil apoptosis.…”
Section: Gc Intracellular Action and On Inflammatory Mediatorsmentioning
confidence: 93%